Parasitological and microbiological evaluation of Lactuca sativa Linnaeus marketed in the municipality of northeastern Brazil (Research, Society and Development, 2020)
The objective of this work was to evaluate the parasites and Escherichia coli in lettuces (Lactuca sativa Linnaeus) sold in open markets in São José de Ribamar-MA. Thirty samples were collected, in the parasitological analysis the sedimentation/centrifugation method was used and the microbiologic the ColiTest® kit and the methylene blue eosin agar medium for Escherichia coli counting. All samples contained some type of protozoan and/or helminth, being the most frequent protozoa Balantidium coli in fair A and Entamoeba coli B. Regarding microbiological aspects, all samples presented total coliforms and Escherichia coli in the sample of vendor 15 of the fair A (3.87 x 102 CFU/mL) and seller 4 of the fair B (2.70 x 102 CFU/mL) showed the highest contamination by this thermololerant. Lettuces marketed are restricted in consumption due to hygienic and sanitary conditions, so understanding the aspects associated with the contamination of these vegetables is important.